Efficacy and safety of thread embedding acupuncture combined with acupuncture for chronic low back pain: A randomized, controlled, assessor-blinded, multicenter clinical trial. Issue 49 (4th December 2020) - Sung, Won-Suk; Hong, Yejin; Jeon, Sae-Rom; Yoon, Jimin; Chung, Eun Kyoung; Jo, Hyeong Geun; Kim, Tae-Hun; Shin, Seungwon; Lee, Hyun-Jong; Kim, Eun-Jung; Seo, Byung-Kwan; Choi, Jieun; et al.
Abstract: Background: Low back pain is a very common disease. Many patients with chronic low back pain (CLBP) have been treated by complementary and alternative medicine such as acupuncture (AT) treatment. A type of AT, thread embedding acupuncture (TEA), consists of a thread that can continually stimulate at the AT points and has mechanical and chemical effects. Although TEA was widely used in clinical practice, there was little evidence of its efficacy and safety for CLBP. Methods: This clinical trial was randomized, controlled, assessor-blinded, two-armed, parallel, and conducted in multiple centers. Four Korean medical institutions recruited 38 outpatients with CLBP. The participants were randomly allocated to a treatment group (TEA combined with AT) or a control group (only AT) in a 1:1 ratio. All participants received conventional AT twice a week for 8 weeks (16 sessions) at 15 AT points (GV3 and bilateral BL23, BL24, BL25, BL26, BL40, BL60, and EX-B5) and the treatment group participants additionally received TEA once a week for 8 weeks (8 sessions) on 10 AT points in the multifidus, spinal erector, and lumbar quadrate muscles. The primary outcome measure of this study was the change of visual analog scale (VAS) from baseline (0 week) to the end of intervention (8 weeks). Secondary outcome measures included clinically relevant improvement (minimal clinically important difference) and 3% to 50% decrease on VAS, disability level (Korean version of Roland and Morris disability questionnaire), quality of life (Korean version of European quality of life 5dimension), global assessment (patient global impression of change), economic analysis, credibility test, and safety assessment. Results: The treatment group showed a significant reduction in VAS scores when compared with the control group (–33.7 ± 25.1 vs –15.6 ± 17.0, P = .013). As for the secondary outcome measures, the treatment group showed significant difference in 50% decrease on VAS and patient global impression of change. There was no serious adverse event associated with TEA and AT. Conclusion: This clinical trial documents the efficacy and safety of TEA combined with AT for the management of CLBP.